2013
DOI: 10.1016/j.bmcl.2013.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Structure activity relationship study of benzo[d]thiazol-2(3H)one based σ receptor ligands

Abstract: Herein we report the SAR study which involved structural modifications to the linker length, aryl substitution and alkylamine ring size of the benzo[d]thiazol-2(3H)one based sigma receptor ( ) ligands. Many compounds in this series displayed low nanomolar affinity for the receptor subtypes. In particular, 8a showed high affinity (−1 Ki = 4.5 nM) for −1 receptors and moderately high selectivity (483 fold) over −2 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[77] These studies revealed the importance of distance between the benzothiazolone core and the pendant piperidine unit, with a shorter chain length to be preferred throughout the series. Alkyl substitutions and a long linker chain resulted in high affinity sigma ligands with low selectivity.…”
Section: Cyclic Amine Ligandsmentioning
confidence: 99%
“…[77] These studies revealed the importance of distance between the benzothiazolone core and the pendant piperidine unit, with a shorter chain length to be preferred throughout the series. Alkyl substitutions and a long linker chain resulted in high affinity sigma ligands with low selectivity.…”
Section: Cyclic Amine Ligandsmentioning
confidence: 99%